KECEPATAN REAKSI PASAR ATAS PUBLIKASI LABA DI BURSA EFEK JAKART: UKURAN PERUSAHAAN DAN TIPE LAPORAN - ISROAH ISROAH (LPPM UNY, 2002)
Abstract The study intends to identify the correlation among the speed of market reaction rate upon the earning announcements with the company size and type of report. The sample used consists of 72 earning announcements of companies registered on the Jakarta Stock Exchange that are select by purposive random sampling. The Kendall’s collection nonparametric statistics are used to test the research hypothesis and descriptive statistic are used to identify the speed of market reaction rate the earning announcements. The empirical results show thatthere are relationships among the speed of market reaction rate upon earning announcement with the company size and type of report show insignificant result. These means that the reaction upon the earnings announcement are not different viewed from the company size and type of report. Themarket reaction upon the small industries is longer (31.60 days) than big industries (23.60 days). The market reaction upon the reporting interim is longer (27.33 days) than reporting annual (16.00 days). Kaywords: earning announcements, speed of market reaction